Genetic engineering of the yeast Saccharomyces cerevisiae to ferment cellobiose - Van Rooyen, Ronel, 1976- (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--Stellenbosch University, 2007.